Respostas
respondido por:
1
( 16)ˣ⁻²⁰ * ( 4)ˣ⁺⁶⁴ = 0
(2⁴)ˣ⁻²⁰ * ( 2²)ˣ⁺⁶⁴
multiplica expoentes
4 * ( x-20) = 4x - 80
2 * ( x + 64) = 2x + 128
reescrevendo
(2)⁴ˣ⁻⁸⁰ * ( 2 )²ˣ⁺¹²⁸
na multiplicação soma os expoentes
( 2)⁴⁺⁻⁸⁰ ⁺ ²ˣ⁺¹²⁸ = ( 2 )⁶ˣ⁺⁴⁸ *** resposta
b
( 36)ˣ⁻⁴² * ( 6 )ˣ⁺²¹⁶
(6²)ˣ⁻⁴² * (6¹)ˣ⁺²¹⁶
2 * ( x - 42) = 2x -84 ***
1 * (x + 216) = x + 216***
reescrevendo
( 6)²ˣ⁻⁸⁴ * ( 6 )ˣ⁺²¹⁶ = ( 6 )²ˣ⁻⁸⁴ ⁺ ˣ⁺²¹⁶ = ( 6 )³ˣ⁺¹³² ****
se ajudei p.f me vote com estrelas
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás